Legal Liability For Holders Of Electricity Supply Business Licenses Without Electrical Safety (A Study At Pln Nusantara Power Umro Medan Power Plant Maintenance Implementation Unit (UPHK) - Hasibuan, Erwin; Maswandi, Maswandi; Frensh, Wenggedes (Fakultas Syariah INSURI Ponorogo, 2025)
This research, entitled